Literary Formula in Novel Mistborn: The Final Empire - I Kadek Harly Mahardikza; Putu Weddha Savitri; I Made Sena Darmasetiyawan (Pusat riset dan Inovasi Nasional, 2025)
This research explores the application of literary formulas in Brandon Sanderson’s novel Mistborn: The Final Empire. The research aims to identify the specific narrative formulas employed within the novel’s structure and to map the pattern by which these formulas are integrated to create its compelling narrative. Using a qualitative approach, the study applies Cawelti’s literary formulas and Vogler’s stages of the journey to analyze key scenes, dialogues, passages, and plot events. Data collection involved close reading and detailed note-taking. The findings show that Mistborn integrates three formulas: adventure, mystery, and romance, into the narrative. By mapping the protagonist’s journey onto Vogler’s twelve stages, the study shows a clear pattern where the adventure formula drives the main plot, the mystery intellectually engages the reader, and the romance provides emotional depth. These findings help explain the narrative appeal of the novel and offer a useful framework for understanding how fantasy stories are structurally composed. The study demonstrates how traditional storytelling formulas can be used to create rich and engaging narratives in modern fantasy literature.